THE ROLE OF SATELLITE CHANNELS IN FORMING TRAFFIC AWARENESS AND PREVENTING ACCIDENTS - A FIELD STUDY: THE ROLE OF SATELLITE CHANNELS IN FORMING TRAFFIC AWARENESS AND PREVENTING ACCIDENTS - A FIELD STUDY (Iraqi Journal of Market Research and Consumer Protection, 2021)
The importance of the research comes from dealing with the problem of lack of traffic awareness, which causes accidents and the occurrence of human and material losses, and the research aims to study the role of satellite channels in forming traffic awareness among the public, and a sample was chosen from Baghdad consisting of (280) individuals, male and female, and used the questionnaire tool. To obtain the data, which included several questions, the results were analyzed statistically and several results were reached, the most important of which is that there is an interest among the public in following traffic programs at a rate of one to two hours to receive information through traffic programs and to identify and apply general rules, and it was found that there is a statistically significant correlation between the extent of follow-up. The sample is for traffic programs and the extent to which satellite channels spread traffic awareness among individuals, and there is a significant correlation between the sample's intensity of watching traffic programs and the level of obtaining information about traffic awareness from television, and there are differences between the sample averages towards the role of satellite channels in spreading traffic awareness.